2007
DOI: 10.1002/oti.223
|View full text |Cite
|
Sign up to set email alerts
|

Client experiences in work rehabilitation in Sweden: a one‐year follow‐up study

Abstract: This study was carried out in a work rehabilitation unit in Sweden, investigated how clients experienced their work rehabilitation process at a one-year follow-up. A semi-structured interview was administered to 14 former clients and a content analysis was applied. Seven categories were derived from the results: 1. Expectations of the rehabilitation process. 2. Social relationships. 3. Client influences on the rehabilitation process. 4. Occupations engaged in during the rehabilitation programme. 5. Perceived o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 22 The literature reviews of RTW interventions have in general found no or only a weak effect of RTW programs which include coordinator support, 23 , 24 whereas others stress the importance of cooperation during the RTW process. 25–27 …”
Section: Introductionmentioning
confidence: 99%
“… 22 The literature reviews of RTW interventions have in general found no or only a weak effect of RTW programs which include coordinator support, 23 , 24 whereas others stress the importance of cooperation during the RTW process. 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…The client on sick leave is dependent on how these authorities work and the decisions they make [ 10 ]; and lack of cooperation and communication among them is an obstacle to the RTW process [ 11 ]. Since vocational rehabilitation programs should be planned in cooperation between the authorities and the clients and designed according to the needs of the client to reach a positive outcome [ 12 ], they may have various designs.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship and cooperation between the client on sick leave and the authorities that work with vocational rehabilitation is important for the client’s RTW [ 12 ]. It has been argued that there is a need for more cooperation between various authorities to better meet the needs of clients on sick leave [ 13 ] and provide them with proper support [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation is recommended to include changes in lifestyle, stress management, and a gradual return to a manageable way of life [24]. Evaluations of rehabilitation programmes in Sweden identify being part of a group and feeling respected by others as essential to promoting health [32], recovery [33][34][35], and return to work [36,37]. Being affected by stress-related exhaustion has a negative impact on patients' health [25], increases the risk for stigmatisation [38], and often involves a longer period of sick leave in relation to other stress-related disorders [24].…”
Section: Introductionmentioning
confidence: 99%